HYBRID FIXED POINT THEORY FOR NONINCREASING MAPPINGS IN PARTIALLY ORDERED METRIC SPACES AND APPLICATIONS - Dhage, B. C.; Dhage, S. B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
We present some hybrid fixed point theorems for nonincreasing mappings in a partially ordered complete metric space and apply to prove the existence as well as an algorithm for the solutions of initial value problems of nonlinear first order ordinary differential equations. An example is also provided to illustrate the abstract theory developed in this paper.